Comparison of progesterone-modified natural cycle and hormone replacement therapy cycle for endometrial preparation in single frozen blastocyst transfer (COMPROSET): protocol for an open-label randomized controlled trial - Yuan, Hai-Ning; Song, Jing-Yan; Sun, Zhen-Gao (Frontiers in Medicine, 2025)
IntroductionAs infertility incidence increases gradually, frozen–thawed embryo transfer (FET) techniques are continuously being developed and enhanced. Although endometrial preparation regimens are strongly linked to live birth rates (LBR), there has been controversy over the ideal regimen. Hormone replacement therapy (HRT) cycles, despite the ease of synchronizing embryo thawing and embryo transfer timing, increase the risk of pregnancies and obstetric complications compared to natural cycles (NC). By ensuring the presence of the corpus luteum while reducing the number of monitoring sessions, the progesterone modified natural cycle (P4mNC) offers more convenience for the patient than the normal NC. This study is designed to compare the effects of P4mNC and HRT cycles on FET outcomes.Methods and analysisThis study is a single-center, open-label, randomized controlled trial (RCT) targeting to recruit a total of 672 women, with 336 individuals each in two arms (1:1 treatment ratio). Women undergoing in vitro fertilization (IVF) scheduled for a single frozen–thawed blastocyst transfer (FBT) and who have regular menstrual cycles are eligible. After signing an informed consent form, patients will be randomized into two groups: the P4mNC group and the HRT group. The primary objective is to determine whether P4mNC-FBT is non-inferior to standard HRT-FBT in terms of LBR. Intention-to-treat analysis will be used for data analysis.Ethics and disseminationThis study is approved by the Institutional Review Board of the Affiliated Hospital of Shandong University of Traditional Chinese Medicine (Reference No. 2024-144-KY). The results of our study will be submitted to reproductive medicine conferences and journals.Clinical trial registrationClinicalTrials.gov, identifier NCT06644794.